Relationship of lowest oxygen saturation value with degree of obstructive sleep apnea on polysomnography - H.M Dwijo Murdiyo; Febrihianto, Ronald Yohanes (Oto Rhino Laryngologica Indonesiana, 2024)
Background: Obstructive sleep apnea (OSA) is a part of sleep disorder breathing syndrome.Symptoms of OSA often occur, but it is difficult to detect. Upon diagnosis, patients generally have hadsymptoms of OSA for years. If it is not treated properly, OSA can lead into complications involvingvarious other organ systems. The standard examination for diagnosing OSA is polysomnography. However,polysomnography examination during the era of Covid-19 pandemic could not be done. Purpose: Todetermine the relationship between the lowest oxygen saturation (SaO2) value and the degree of obstructivesleep apnea on polysomnography examination. Method: Observational analytic study with a crosssectional approach. The total sample was 59 subjects, consisted of 37 males and 22 females. The lowestSaO2 was assessed on polysomnography examination and compared with the degree of OSA. Result:The lowest SaO2 relationship with the degree of OSA showed a significant negative result with a strongrelationship. In mild OSA, the Area Under Curve (AUC) value = 77.1%, and the cut off SaO2 value wasobtained at 90.5%. In moderate OSA, the AUC = 85% and the cut off SaO2 value was at 87.5%. In severeOSA, the AUC value was 94% and the cut off SaO2 value was obtained at 84.5%. Conclusion: Therewas a significant relationship between the lowest oxygen saturation on polysomnography examinationand the degree of OSA.